Gas formation and biological effects of biodegradable magnesium in a preclinical and clinical observation. Issue 1 (31st December 2018) - Kim, Yu-Kyoung; Lee, Kwang-Bok; Kim, Seo-Young; Bode, Ken; Jang, Yong-Seok; Kwon, Tae-Young; Jeon, Moo Heon; Lee, Min-Ho
Abstract: Magnesium alloys are biodegradable metals receiving increasing attention, but the clinical applications of these materials are delayed by concerns over the rapid corrosion rate and gas formation. Unlike corrosion, which weakens mechanical properties, the gas formation issue has received little attention. Therefore, we evaluated the gas formation and biological effects for Mg implants through preclinical (immersed in Earle's balanced salt solution and in vivo ) and clinical studies. The immersion test examined the gas volume and composition. The in vivo study also examined gas volume and histological analysis. The clinical study examined the gas volume and safety after Mg screw metatarsal fixation. Gas was mainly composed of H2, CO and CO2 . Maximum volumes of gas formed after 5 days for in vivo and 7 days in clinical study. Within the clinical examination, two superficial wound complications healed with local wound care. Osteolytic lesions in the surrounding metaphysis of the Mg screw insertion developed in all cases and union occurred at 3 months. Mg implants released gas with variable volumes and composition (H2, CO, and CO2 ), with no long-term toxic effects on the surrounding tissue. The implants enabled bone healing, although complications of wound breakdown and osteolytic lesions developed. Abstract :